2022
DOI: 10.3389/fpsyg.2022.992935
|View full text |Cite
|
Sign up to set email alerts
|

Affective and cognitive brain-networks are differently integrated in women and men while experiencing compassion

Abstract: Different theoretical models have proposed cognitive and affective components in empathy and moral judgments encompassing compassion. Furthermore, gender differences in psychological and neural functions involving empathic and moral processing, as well as compassionate experiences, have been reported. However, the neurobiological function regarding affective and cognitive integration underlying compassion and gender-associated differences has not been investigated. In this study, we aimed to examine the intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…We may review the cases of two virtues, i.e., compassion and honesty, with neurallevel evidence. First, fMRI studies have demonstrated that considering and deliberating upon the virtue of compassion was significantly associated with activity in mirror neuron regions (Kim et al 2021;Rodríguez-Nieto et al 2022). The meta-network of moral functioning consisting of the DMN, SN, and CEN showed significant interaction and connectivity with the mirror neuron regions.…”
Section: Addressing Concerns On Phronesis Based On Neuroscientific Ev...mentioning
confidence: 99%
“…We may review the cases of two virtues, i.e., compassion and honesty, with neurallevel evidence. First, fMRI studies have demonstrated that considering and deliberating upon the virtue of compassion was significantly associated with activity in mirror neuron regions (Kim et al 2021;Rodríguez-Nieto et al 2022). The meta-network of moral functioning consisting of the DMN, SN, and CEN showed significant interaction and connectivity with the mirror neuron regions.…”
Section: Addressing Concerns On Phronesis Based On Neuroscientific Ev...mentioning
confidence: 99%
“…In contrast, little research has been done on what the brains of people who accept such diversity are like. However, compassion is necessary to realize a society in which women and LGBTQ people are active, and compassion is said to be the ability to empathize with other people's suffering (Rodríguez-Nieto et al, 2022). Therefore, it is not impossible to hypothesize and analyze the relationship between brain health and understanding of diversity by referring to the mechanisms of empathy that have been dealt with in the field of brain science.…”
Section: Introductionmentioning
confidence: 99%